Coronal magnetic field profiles from shock‐CME standoff distances. Issue 10 (8th October 2016) - Schmidt, J. M.; Cairns, Iver H.; Gopalswamy, N.; Yashiro, S.
Abstract: Coronagraphs observe coronal mass ejections (CMEs) and driven shocks in white light images. From these observations the shock's speed and the shock's standoff distance from the CME's leading edge can be derived. Using these quantities, theoretical relationships between the shock's Alfvénic Mach number M A and standoff distance, and empirical radial profiles for the solar wind velocity and number density, the radial magnetic field profile upstream of the shock can be calculated. These profiles cannot be measured directly. We test the accuracy of this method for estimating the radial magnetic field profile upstream of the shock by simulating a sample CME that occurred on 29 November 2013 using the three‐dimensional (3‐D) magnetohydrodynamic Block‐Adaptive‐Tree‐Solarwind‐Roe‐Upwind‐Scheme code, retrieving shock‐CME standoff distances from the simulation, and comparing the estimated and simulated radial magnetic field profiles. We find good agreement between the two profiles (within ±30%) between 1.8 and 10 R ⊙ . Our simulations confirm that a linear relationship exists between the standoff distance and the inverse compression ratio at the shock. We also find very good agreement between the empirical and simulated radial profiles of the number density and speed of the solar wind and inner corona. Key Points: Numerical test of standoff distance Mach number relationship Numerical test of Mach number magnetic field strength relationship Global simulation of CME and shock system with derived quantities